Experimental Performance Investigation of Double-layer Shields at Power Frequency Magnetic Shielding - Koroglu, Selim; Umurka, Nurettin; Kilic, Osman (IEEE, 2008)
Double-layer shields have received attention in magnetic shielding at extremely low frequency. Also, cylindrical shape is one of shielding structures widely used in industry. In this study, cylindrical shaped shields with commonly available and inexpensive materials used for power frequency magnetic field shielding. The magnetic shielding performances are investigated experimentally for single and double-layer shields at power frequencies. The aim of this work is to extend the discussion in the area of shielding performance of the double-layer shields.
Keywords: Magnetic shielding; double-layer shields; power frequency; Energy & Fuels; Engineering